INTERRELATION AND INTERDEPENDENCE OF PEDAGOGICAL CULTURE AND COMPETENCE OF FOREIGN LANGUAGE TEACHERS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The world practice of teaching English has demonstrated great interest in the study of the pedagogical competence of an English language teacher of a higher educational institution, since pedagogical competence and pedagogical culture are today considered as the most important attributes of the implementation of professional and educational activities. This article describes about interrelation and interdependence of pedagogical culture and competence of foreign language teachers.